Peningkatan Motivasi Belajar Melalui Penerapan E-Modul Fisika Berbasis Flipped Learning - Yohana Atwina Aspiranti Ndoa; Jumadi Jumadi (Postgraduate, University of Mataram, 2022)
Face-to-face learning is being enforceable limitedly. To improve the quality of time in class, teachers can apply the flipped learning method. Flipped learning combines face-to-face in class with online learning. Physics e-module are acceptable as independent teaching material for students before participating in learning activities in class. The learning process in class gets used for discussion and practicum. This research implementation to know the application of physics e-modules based on flipped learning to increase students' learning motivation. This type of research is a pre-experimental type one-group pretest-posttest design. The samples were 16 students in class X Mathematics and Natural SciencesÂ atÂ Public Senior High School Wolowae. The data collection instruments used were questionnaire validation sheets and student learning motivation questionnaires. Based on data analysis, Asymp.Sig. (2-tailed) obtained is 0.00 < 0.05. Thus, there are differences in students' learning motivation before and after of physics e-module based on flipped learning. The increase of students' learning motivation with the acquisition N-Gain value was 0.64. This increase includes the medium category. The application of a physics e-module based on flipped learning in physics learning, especially the material of quantities and measurements, can increase the learning motivation of high school students in class X